Determinan Pengangguran Usia Muda Terdidik di Provinsi Banten Tahun 2020 - Faiz Alwan Alharis; Aisyah Fitri Yuniasih (Politeknik Statistika STIS, 2022)
Banten Province is the province with the highest open unemployment rate in Indonesia. In 2020, the open unemployment rate in Banten Province reached 10.64 percent. The high unemployment rate is dominated by the workforce aged 16 to 30 years. The high unemployment at a young age, especially unemployment at an educated youth can be the emergence of economic problems in Banten Province. This problem can be caused by the characteristics of the individual or the characteristics of the region. To be able to determine the effect of these characteristics, multilevel binary logistic regression analysis was used. The results obtained indicate that all variables significantly affect youth educated unemployment in Banten Province. The educated young age workforce that tends to become unemployed is the workforce that has the characteristics of living in rural areas, not married, not the head of the household, has never attended certified training, has work experience, lives in a district/city with a large population, and lives in districts/cities with low GRDP.